Human Herpesvirus 6 is Associated with Status Epilepticus and Hyponatremia after Umbilical Cord Blood Transplantation - Fernanda Leite de Souza Franceschi; Jaime Green; Zuzan Cayci; Evan Mariash; Mustapha Ezzeddine; Veronika Bachanova; Celalettin Ustun (Canadian Journal of Infectious Diseases and Medical Microbiology)
Status epilepticus after allogeneic hematopoietic cell transplantation (alloHCT) is rare. The authors report a case involving a 65-year-old man with nonconvulsive status epilepticus 34 days after umbilical cord blood transplantion for chronic lymphocytic leukemia. Cerebrospinal fluid and serum were positive for human herpesvirus 6 (HHV6). Magnetic resonance imaging of the brain showed symmetric T2 hyper-intensity bilaterally in the mesial temporal lobes, and T2 hyperintensi-ties and restricted diffusion of bilateral putamina. Despite aggressive anticonvulsive therapy, his seizures only abated with initiation of ganciclovir therapy. The patient completed six weeks of combination antiviral therapy (ganciclovir and foscarnet). His cognitive function gradually improved and, after prolonged rehabilitation, the patient was discharged home with residual intermittent memory loss but otherwise functional. HHV6 should be considered in the differential diagnosis of nonconvulsive status epilepticus after alloHCT, especially in patients with hyponatremia. Empirical antiviral therapy targeting HHV6 should be administered to these patients.